1999
DOI: 10.1111/j.2042-3306.1999.tb05293.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an endurance ride on metabolism and neutrophil function

Abstract: SummaryThe effects of an endurance ride on neutrophil functions in endurance-trained horses were evaluated and related to metabolic changes and changes in cortisol concentrations. Blood samples were taken from 7 horses (aged 9-15 years) one day before, and then 30-60 min, 1 day and 8 days after the ride. The race resulted in elevated serum cortisol levels (<465 nmoy1) and an increased neutrophiklymphocyte ratio.Immediately post race, the neutrophil ability to engulf yeast was increased. One day after the race,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 15 publications
4
13
2
1
Order By: Relevance
“…Studies of adaptive immunity are less frequent and related to lymphocyte proliferation after specific or non-specific stimulation, and the dosage of cytokines, as well as to the production of antibody. 9,19,21 The observations reported in the horses are rather similar to those observed in humans: namely • an intense -or prolonged -effort is associated with an early neutrophil burst (and leukocytes in general); secretion of pro-inflammatory cytokines during exercise and augmentation of LAK activity [22][23][24] • a later impairment of the innate immunity during the recovery period. 10,16,25,26,27,28 …”
Section: Effect Of Exercisesupporting
confidence: 59%
“…Studies of adaptive immunity are less frequent and related to lymphocyte proliferation after specific or non-specific stimulation, and the dosage of cytokines, as well as to the production of antibody. 9,19,21 The observations reported in the horses are rather similar to those observed in humans: namely • an intense -or prolonged -effort is associated with an early neutrophil burst (and leukocytes in general); secretion of pro-inflammatory cytokines during exercise and augmentation of LAK activity [22][23][24] • a later impairment of the innate immunity during the recovery period. 10,16,25,26,27,28 …”
Section: Effect Of Exercisesupporting
confidence: 59%
“…A recent study on horses performing endurance rides indicates that horses also rely to a greater extent on glycogenolysis in the MG pool (Essén-Gustavsson and Jensen-Waern 2002). It is probable that MG is readily degraded in type I and IIA fibres as they have been shown to be preferentially glycogen depleted after exercise of endurance nature (Snow et al 1981;Sherman et al 1983;Jensen-Waern et al 1999). However, with exercise of short intense type, studies on both human and horse have shown that glycogen is degraded not only in type I and type IIA fibres but also in type IIB fibres (Essén 1978;Valberg 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Depois do aumento transitório do número de linfócitos existe outro aumento de leucócito relacionado com uma pequena linfopenia e uma forte neutrofilia, resultante da liberação de um pool de granulócitos e aumento da liberação destas células pela medula óssea (Persson 1983). Acredita-se que a mudança na cinética leucocitária, manifestada pelo aumento da rela- ção neutrófilo/linfócito, está relacionada com o aumento da concentração de hormônio adrenocortical, principalmente, cortisol no sangue (Jensen-Waern et al 1999, Robson et al 2003. Este hormônio não estimula somente a produção de neutrófilo pela medula óssea e sua liberação para o sangue periférico, mas também inibe a migração destas células para o espaço intravascular (Pyne 1994) e interfere no número de linfócitos circulantes (Shinkai et al 1996).…”
Section: Quadro 3 Médias Dos Momentos I E Ii E Das Relações Mi/mii Dunclassified